2008
DOI: 10.1007/s11306-008-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of the interaction between plants and herbivores

Abstract: Insect herbivores by necessity have to deal with a large arsenal of plant defence metabolites. The levels of defence compounds may be increased by insect damage. These induced plant responses may also affect the metabolism and performance of successive insect herbivores. As the chemical nature of induced responses is largely unknown, global metabolomic analyses are a valuable tool to gain more insight into the metabolites possibly involved in such interactions. This study analyzed the interaction between feral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 61 publications
2
99
0
Order By: Relevance
“…In this study, 127 different metabolites were identified and measured based on GC-TOF-MS. Second, detecting the changes in the important metabolites at different time points could assist in elucidating the roles of these metabolites in the modulation dynamics of the ecosystem. Third, the chemical composition of the environment (i.e., agar) could also be monitored to reveal metabolic cooperation due to its role in metabolite exchanges (15,24). Research on metagenomics and metaproteomics usually deduced the role of some organism in the ecosystem based on gene or protein analysis, but the metabolomics approach would provide a more intuitive understanding of how cells interact with each other via metabolites and the cellular responses to environments.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 127 different metabolites were identified and measured based on GC-TOF-MS. Second, detecting the changes in the important metabolites at different time points could assist in elucidating the roles of these metabolites in the modulation dynamics of the ecosystem. Third, the chemical composition of the environment (i.e., agar) could also be monitored to reveal metabolic cooperation due to its role in metabolite exchanges (15,24). Research on metagenomics and metaproteomics usually deduced the role of some organism in the ecosystem based on gene or protein analysis, but the metabolomics approach would provide a more intuitive understanding of how cells interact with each other via metabolites and the cellular responses to environments.…”
Section: Discussionmentioning
confidence: 99%
“…31), including the attack of insects (32)(33)(34); but few of these studies have explored qualitative and quantitative variations of these metabolic adjustments across native populations. To systematically explore natural diversity patterns in the metabolic response to Manduca sexta herbivory of different N. attenuata populations, we conducted a glasshouse-based high-throughput MS-based metabolomics approach on 183 plants derived from seeds collected in Utah, Nevada, Arizona, and California.…”
Section: Significancementioning
confidence: 99%
“…The metabolomics approach has been applied in various areas of plant biology and ecology (Sardans et al, 2011;Weckwerth, 2011), where it has helped in understanding the regulation of pathways during plant-herbivore interactions (Jansen et al, 2008;Misra et al, 2010) and plant stress responses (Shulaev et al, 2008;Nakabayashi and Saito, 2015). What typically distinguishes metabolomics from targeted analyses or general metabolic profiling is the ambition to integrate with other omics sciences (Fiehn, 2002;Barah and Bones, 2015).…”
mentioning
confidence: 99%